Conducted emission evaluation for direct matrix converters - Nothofer, A.; Tarisciotti, Luca; Greedy, Steve; Empringham, Lee; De Lillo, Liliana; Degano, M. (2016)
Matrix converters have been recently proposed as an alternative solution to the standard back-to-back converter in aerospace applications. However, Electromagnetic Interference (EMI), in particular, conducted emissions represent a critical aspect for this converter family. Direct Matrix Converter (DMC) are usually modelled only at the normal operating frequency, but for the research presented in this paper, the model is modified in order to include a detailed high frequency description, which is of interest for conducted emission studies. This paper analyzes the performance of DMC, when different control and modulation techniques are used. Experimental results are shown to validate the simulation models.